Hukum Musik dari Angklung menurut Islam: Sebuah Analisis Fiqih dan Kontekstual - A Wathon (Lembaga Yasin AlSys, 2025)
Although the legal status of music in Islam has been widely discussed in previous research, studies that specifically examine the legal status of traditional musical instruments such as the angklung from the perspective of contemporary fiqh remain limited. This study aims to comprehensively analyze classical and modern scholars’ views on music and its instruments and to apply these views to the distinctive characteristics of the angklung as cultural heritage and a medium of artistic expression. It employs a qualitative design with a literature study (library research) approach and fiqh muqaranah (muqaranah fiqhiyyah) analysis of relevant dalil syar‘i and contemporary fatwas. The findings show a broad spectrum of opinions, ranging from absolute prohibition to conditional permissibility, which depends greatly on the context, purpose, and impact of the music. More specifically, the study indicates that the angklung, as an instrument commonly used in educational, da‘wah, and cultural preservation contexts without elements of wrongdoing, tends to be categorized as a permissible form of art by most contemporary scholars. These findings contribute to the development of the theory of fiqh al-wāqi‘ (fiqh of reality) and broaden understanding of the interaction between Islamic law, culture, and art. The study concludes that it is essential to consider maqāṣid al-syarī‘ah (the objectives of Islamic law) and ‘urf (customary practice) in legal determinations and encourages religious institutions and cultural practitioners to collaborate in educating the public about the shar‘i boundaries of artistic practice. The implications of this research include theoretical contributions to enriching the literature on the fiqh of music and culture, as well as practical implications for government, educational institutions, and arts communities in developing angklung performance practices that are aligned with Islamic values, while also opening further opportunities to explore contemporary fiqh issues in other artistic and cultural contexts.